Միջնադարյան գրիչ-ծաղկողները Գ. Դևրիկյանի ստեղծագործություններում - Աննա Երկանյան (ՀՀ ԳԱԱ հրատ.)
Геворк Деврикян в своих произведениях, и в романах, и в исторических рассказах, и в публицистических статьях, придает особое значение образу верных национальному духу писцов-миниатюристов, которыми двигало великое стремление быть полезными родной стране и грядущим поколениям. Gevorg Devrikyan in his works, either in novels or historical stories and publicistic articles, attaches particular importance to the personages of the scribesminiaturists, who were faithful to the national spirit and driven by a great desire to be useful to their native country and to future generations.
Keywords: Fine Arts; Painting; Language and Literature; Criticism